A Liouville theorem for some Bessel generalized operators - Galli, Vanesa Gisele (2018)
In this paper we establish a Liouville theorem in (Formula presented.) for a wider class of operators in (Formula presented.) that generalizes the n-dimensional Bessel operator. We will present two different proofs, based in two representation theorems for certain distributions ‘supported in zero’.